Growth and developmental delay risk factors among under-five children in an inner-city slum area - Hartono Gunardi; Resyana P. Nugraheni; Annisa R. Yulman; Soedjatmiko Soedjatmiko; Rini Sekartini; Bernie E. Medise; Angga Wirahmadi; Elizabeth Melina (Indonesian Pediatric Society, 2019)
Background Growth and developmental delays are common among children under the age of five years (under-five children), especially in slum areas. Early detection and intervention may give better prognoses. Objective To detect growth and developmental delays and related risk factors among under-five children living in an inner-city slum area of the Indonesian capital. Methods This cross-sectional study was conducted from October to November 2018 in Tanah Tinggi, Johar Baru District, an inner-city slum area in Central Jakarta. Subjects were healthy children aged 3–60 months. Socioeconomic profile was obtained through questionnaires, anthropometric data through measurements, and developmental status through the Kuesioner Pra Skrining Perkembangan (KPSP) instrument. Development was considered to be delayed for KPSP scores <9. Data were analyzed using Chi-square test. Results Of 211 subjects, prevalence of underweight, stunting, and wasting were 35.1%, 28.0%, and 20.9%, respectively, meanwhile low maternal education, and low family income were 57.9% and 75%. The prevalence of developmental delay was 10%, while suspected developmental delay was 26.1%. The prevalence increased from age 21 months and peaked at 36 months. Associated risk factors were low maternal education, low family income, underweight weight-for-age, stunted height-for-age, and microcephalic head circumference-for-age. Conclusion Low education and low income were significant risk factors for growth and developmental delay.